PERGULATAN HALAQOH: Model dan Pola Dalam Berdakwah - Moh. Dahlan (JURNAL ILMIAH SYI'AR, 2014)
The diversity of Indonesian citizens is historical-empirical reality. That’s why, to build  plural life can not be built without a solid rationale. Theoretical framework of this study is thought of  Ian G. Barbour that divides the four typologies: First, the conflict approach. Second, the independence approach. Third, dialogue approach. Fourth, the integration approach. The scientific methodology  that is used is descriptive, whereas the method of analysis used is the qualitative analysis. The study indicates that the Islamic scholarly discourse developed based on the analysis or cross-disciplinary approach, so it can be born scientific scholarly discourse in halaqah that is able to support a dynamic and inclusive religion. One of them is a dynamic and progressive Halaqah in Islamic Organization of NU that has made some of the decisions, such as the recognition of legitimacy of the Republic of Indonesia and the Pancasila in accordance with the Islamic guidance.